Efficient CO2 capture by tertiary amine-functionalized ionic liquids through Li+-stabilized zwitterionic adduct formation - Yang, Zhen-Zhen; He, Liang-Nian (Beilstein Journal of Organic Chemistry, 2014)
Highly efficient CO2 absorption was realized through formation of zwitterionic adducts, combining synthetic strategies to ionic liquids (ILs) and coordination. The essence of our strategy is to make use of multidentate cation coordination between Li+ and an organic base. Also PEG-functionalized organic bases were employed to enhance the CO2-philicity. The ILs were reacted with CO2 to form the zwitterionic adduct. Coordination effects between various lithium salts and neutral ligands, as well as the CO2 capacity of the chelated ILs obtained were investigated. For example, the CO2 capacity of PEG150MeBu2N increased steadily from 0.10 to 0.66 (mol CO2 absorbed per mol of base) through the formation of zwitterionic adducts being stabilized by Li+.
Keywords: carbon capture and sequestration; CO2 chemistry; coordination effect; ionic liquid; polyethylene glycol; zwitterionic adducts